THE INFORMATION SPACE ASPECTS OF MODERN HIGHER EDUCATION - Булгакова, Н. Б. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
Education in the information society is seen as a common information space which promotes understanding of systemic connections of new knowledge, forms the world outlook for future professionals in higher education